Learning Physics Using a Contextual Teaching and Learning Approach to Children with Physical Impairment - Supartin Supartin; Asri Arbie; Trisnawaty Junus Buhungo; Sukri Katili (STKIP Singkawang, 2023)
This study aims to see the effect of the Contextual teaching and learning model on science learning for disabled children. The learning devices use the Contextual Teaching and Learning (CTL) approach and the PBI (Problem Based Instruction) learning model for disabled children in class X SMA which consists of the syllabus , RPP, LKPD, teaching materials and competency assessment. This research is a type of research and development using the ADDIE development model which consists of 5 stages, namely the Analysis, Design, Development, Implementation, and Evaluation stages. This study uses data collection consisting of expert validation, observation, interviews and tests. Based on the results of the study, it was found that the learning tools that had been developed met the appropriate criteria and could be used with minor revisions. Decent learning tools were obtained from validation results by 3 validators who were test lecturers, while the effectiveness of the devices was obtained from several indicators, namely learning implementation with an average of 93.93%, student activity with an average of 86.9%. As well as positive responses from teachers and students obtained by interview.